GOOD MANUFACTURING PROCEDURES (GMPS) IN THE HERB FOOD AND MEDICINAL PLANT INDUSTRY. ACTUAL SITUATION AND PARTICULARITIES. - van Ginkel, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The Good Agricultural Practices (GAP) and the Good Manufacturing Procedures (GMP) of Medicinal and Aromatic Plants (MAP) apply to growing, primary processing and manufacturing of MAP products and their derivatives, for humans and/or animals (EMEA, EC). GMPs are a key aspect of the quality assurance system, and aims to ensure that medicinal products are consistently manufactured and tested according to pre-defined quality standards as required by the health authorisation or product specification guidelines. This minimizes the probability of contamination and adulteration, mix-ups and errors, batch to bath variability and helps enhancing final quality, efficacy and security. In the practice, it is difficult to know when to apply the GMPs in the MAP industry. The aim of this work is to make an exhaustive bibliographic compilation of guidelines and documents related to GMPs and GAPs in the MAP industry, and point the particularities specific of herb products. There are some guidelines and documents from EMEA, WHO, FDA, ICH, MHLW, PIC/S, APIC – CEFIC, IPEC-PQG and EHPM. On an international level, documents have been harmonized and formally affected by the ICH and adopted by the EU, MHLW and FDA. Some committees, organisations, federations and councils, also make GMP guidelines. Some aspects are specific of the MAP industry and will lead to special procedures and check lists for GMP and GAP inspections.